2020
DOI: 10.3390/ijerph17217762
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Prolonged Second Stage of Labor and Short-Term Neonatal Morbidity: A Systematic Review and Meta-Analysis

Abstract: To evaluate the association between prolonged second stage of labor and the risk of adverse neonatal outcomes with a systematic review and meta-analysis. PubMed, Scopus and EMBASE were searched using the search strategy “Labor Stage, Second” AND (length OR duration OR prolonged OR abnormal OR excessive). Observational studies that examine the relationship between prolonged second stage of labor and neonatal outcomes were selected. Prolonged second stage of labor was defined as 4 h or more in nulliparous women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Traditionally labour duration is divided into first and second stage. Several efforts have been made to understand how these two stages of labour influence birth outcomes 1,4,6,24,25 . Labour is a continuous process, which needs be taken into consideration since duration spent at each stage jointly shape labour management decisions and subsequent maternal and neonatal birth outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally labour duration is divided into first and second stage. Several efforts have been made to understand how these two stages of labour influence birth outcomes 1,4,6,24,25 . Labour is a continuous process, which needs be taken into consideration since duration spent at each stage jointly shape labour management decisions and subsequent maternal and neonatal birth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several efforts have been made to understand how these two stages of labour influence birth outcomes. 1,4,6,24,25 Labour is a continuous process, which needs be taken into consideration since duration spent at each stage jointly shape labour management decisions and subsequent maternal and neonatal birth outcomes. As we applied a non-parametrical modelling approach on the continuous duration of active first stage, we found a linear increase in second-stage duration up until active first-stage duration of 12 h. This was further shown in the detailed curves for the 80 th and 90 th quantiles (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Low neonatal Apgar scores and foetal acidosis are reportedly associated with several perinatal factors 7 , 8 , and the labour environment around the foetus is closely associated with the incidence of low neonatal Apgar scores and foetal acidosis. Prolonged labour duration (LD) affects the incidence of neonatal morbidity 9 , 10 and results in low Apgar scores 10 . However, several studies have indicated that a prolonged first stage of labour is not associated with an increased incidence of adverse neonatal outcomes 11 , 12 and that a prolonged second stage of labour is not associated with an increased incidence of low neonatal Apgar scores and foetal acidosis 13 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The spontaneous pushing reflex of the pregnant woman comes after the full dilation of the cervix (2)(3)(4)(5). In literature, it is stated that starting to push before the urge to push and encouraging the woman to push can lead to constant exhausting pushings, which may result in maternal fatigue and exhaustion, and therefore the risk of cesarean delivery may increase (3,6). Cesarean delivery may decrease maternal and infant mortality, and complications such as obstetric fistula.…”
Section: Introductionmentioning
confidence: 99%